Pengaruh literasi keuangan terhadap kinerja keuangan UMKM makanan skala kecil di Kota Cirebon dengan kapabilitas digital sebagai variabel mediasi - Nugroho, Ridho Dwi; Budianto, Erwin; Dhevyanto, Benny (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2026)
This study examines the effect of financial literacy on the financial performance of food micro, small, and medium enterprises (MSMEs) in Cirebon City, with digital capability as a mediating variable. A quantitative approach was employed, utilizing primary data collected from 100 food MSME owners through purposive sampling and a closed-ended Likert-scale questionnaire. Financial literacy was operationalized across three dimensions: financial understanding, financial skills, and financial knowledge. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that all three dimensions of financial literacy have a positive and significant impact on financial performance. Furthermore, financial literacy positively and significantly influences digital capability, which in turn positively affects financial performance. Digital capability partially mediates the relationship between financial literacy and financial performance. By disaggregating financial literacy into three independently measured constructs and positioning digital capability as a mediating mechanism, this study offers novel empirical insights, particularly within the underexplored context of small-scale food MSMEs in Cirebon City